2018
DOI: 10.1371/journal.pone.0191027
|View full text |Cite
|
Sign up to set email alerts
|

Fire forbids fifty-fifty forest

Abstract: Recent studies have interpreted patterns of remotely sensed tree cover as evidence that forest with intermediate tree cover might be unstable in the tropics, as it will tip into either a closed forest or a more open savanna state. Here we show that across all continents the frequency of wildfires rises sharply as tree cover falls below ~40%. Using a simple empirical model, we hypothesize that the steepness of this pattern causes intermediate tree cover (30‒60%) to be unstable for a broad range of assumptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 66 publications
4
61
0
1
Order By: Relevance
“…Indeed, both fires and herbivores show a steep increase in abundance below a critical tree cover (Figure a,e). It is this shape that allows for the existence of alternative stable states under a range of assumed growth and loss curves for tree cover (Kitzberger, Aráoz, Gowda, Mermoz, & Morales, ; Van Nes et al., ; also see Supporting Information Figure S9). This parallel structure of the two feedbacks is worth highlighting, but it is important to also recognize their differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, both fires and herbivores show a steep increase in abundance below a critical tree cover (Figure a,e). It is this shape that allows for the existence of alternative stable states under a range of assumed growth and loss curves for tree cover (Kitzberger, Aráoz, Gowda, Mermoz, & Morales, ; Van Nes et al., ; also see Supporting Information Figure S9). This parallel structure of the two feedbacks is worth highlighting, but it is important to also recognize their differences.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from differences between ecosystem types, there are differences among continents in ecosystem structure (Xu et al., ) and in fire ecology (Lehmann et al., ). For example, fire frequency is relatively high in Africa (Giglio, Randerson, & van der Werf, ; Van Nes et al., ), although that may be counteracted by relatively low fire intensity (Dantas & Pausas, ) and relatively high recovery from disturbances in that continent (Schwalm et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, van Nes et al. ) are widely prevalent in nature. Studies have shown that systems with high positive feedback among individuals are likely to be bistable (Xu et al.…”
Section: Methodsmentioning
confidence: 99%